STATE-OWNED ASSETS AS A PILLAR OF NATIONAL REVENEU: A COMPREHENSIVE ANALYSIS - Dewi Citra Ayu Lestari; Dwi Nurul Hidayati (Assets Journal: Journal of Economic and Business, 2026)
This paper examines the concept of state ownership as a source of national revenue within the framework of Islamic economic principles. It delves into the classification of state revenue sources, including kharaj, jizyah, 'usyur, khumus rikaz, and dharibah (taxes), as well as their unique characteristics and applications in an Islamic context. These revenue types are grounded in Shariah, which dictates specific rules for their collection and utilization to ensure justice and societal welfare. The study highlights the temporary and conditional nature of taxes, which are levied in cases of fiscal shortfalls and are limited to wealthy Muslims for addressing communal needs. Furthermore, it explores the principles of fiscal management in Islam, emphasizing fairness, transparency, and the prioritization of public interests. By integrating Islamic teachings with contemporary fiscal policies, this research underscores the potential for a balanced economic system that aligns with spiritual and social values.